Beta-Blockers and Oxidative Stress in Patients with Heart Failure - Kazufumi Nakamura; Kenki Enko; Kei Yunoki; Daiji Miura; Masato Murakami; Hiroshi Ito; Tohru Ohe; Hiromi Matsubara; Kengo F Kusano; Hiroshi Morita; Kunihisa Kohno; Satoshi Nagase; et al. (MDPI AG, 2011)
Oxidative stress has been implicated in the pathogenesis of heart failure. Reactive oxygen species (ROS) are produced in the failing myocardium, and ROS cause hypertrophy, apoptosis/cell death and intracellular Ca2+ overload in cardiac myocytes. ROS also cause damage to lipid cell membranes in the process of lipid peroxidation. In this process, several aldehydes, including 4-hydroxy-2-nonenal (HNE), are generated and the amount of HNE is increased in the human failing myocardium. HNE exacerbates the formation of ROS, especially H2O2 and ·OH, in cardiomyocytes and subsequently ROS cause intracellular Ca2+ overload. Treatment with beta-blockers such as metoprolol, carvedilol and bisoprolol reduces the levels of oxidative stress, together with amelioration of heart failure. This reduction could be caused by several possible mechanisms. First, the beta-blocking effect is important, because catecholamines such as isoproterenol and norepinephrine induce oxidative stress in the myocardium. Second, anti-ischemic effects and negative chronotropic effects are also important. Furthermore, direct antioxidative effects of carvedilol contribute to the reduction of oxidative stress. Carvedilol inhibited HNE-induced intracellular Ca2+ overload. Beta-blocker therapy is a useful antioxidative therapy in patients with heart failure.